Educação em direitos humanos e o debate de gênero no sistema público de ensino básico de Cajazeiras - PB : um estudo sobre a (in)efetividade das políticas públicas municipais em educação - Torres, Victor de Saulo Dantas (2017)
Considered the history of rights violations of certain social groups based on gender and sexual differences, especially women and LGBT people, it is not difficult to see that the exclusionary structure, that operates and reinforces the discriminatory treatment of these groups, found in social institutions, especially in the education ones, the necessary support to perpetuate such forms of acting and thinking. Pondering our school experiences front of the conditioning of identities and sexualities to a binary and heteronormative model, in addition to the approach with the theme in academic production and the constant discussion about how the school should position itself in the new diversity paradigm, we chose to deepen the studies on the perspective of public policies on Human Rights, knowing that these instruments are essential for social transformation, so that, in this regard, our research has returned to the field of public policies in Human Rights Education. Thus, the present dissertation have as main objective ascertaining the effectiveness of public education policies in the field of gender and diversity in the municipality of Cajazeiras-PB, face the inclusion of this theme in its Municipal Education Plan and other actions in this direction developed in the municipal school system. For that, a qualitative study was developed, with not structured interviews, with 13 subjects, between representatives of social movements, executive and legislative power, being 04 of them teachers of the own municipal system, besides the documentary, bibliographical and field research, this last through school observation, and the interpretation of the data was done by the technique of content analysis. Was analyzed the gender and diversity policies in the city and its influence in the school curriculum, in particular the reinforcement or discouragement of certain practices and prejudices based on gender and sexuality, discussing the quality of these policies in the context of municipal education, identifying as main results the existence of fragile policies with reflections on some educators actuation, showing that there’s still a lot to work at this sense. For last, the research indicates new perspectives of deepen, in order to understand how will be developed the continuing formation in gender and diversity of municipal teachers, foreseen on the MEP of Cajazeiras-PB.